Whey- and Soy Protein Isolates Added to a Carrot-Tomato Juice Alter Carotenoid Bioavailability in Healthy Adults - Mohammed Iddir; Denis Pittois; Cédric Guignard; Bernard Weber; Manon Gantenbein; Yvan Larondelle; Torsten Bohn (MDPI AG, 2021)
Recent findings suggested that proteins can differentially affect carotenoid bioaccessibility during gastro-intestinal digestion. In this crossover, randomized human trial, we aimed to confirm that proteins, specifically whey- and soy-protein isolates (WPI/SPI) impact postprandial carotenoid bioavailability. Healthy adults (n = 12 males, n = 12 females) were recruited. After 2-week washout periods, 350 g of a tomato-carrot juice mixture was served in the absence/presence of WPI or SPI (50% of the recommended dietary allowance, RDA ≈ 60 g/d). Absorption kinetics of carotenoids and triacylglycerols (TAGs) were evaluated via the triacylglycerol-rich lipoprotein (TRL) fraction response, at timed intervals up to 10 h after test meal intake, on three occasions separated by 1 week. Maximum TRL-carotenoid concentration (Cmax) and corresponding time (Tmax) were also determined. Considering both genders and carotenoids/TAGs combined, the estimated area under the curve (AUC) for WPI increased by 45% vs. the control (p = 0.018), to 92.0 ± 1.7 nmol × h/L and by 57% vs. SPI (p = 0.006). Test meal effect was significant in males (p = 0.036), but not in females (p = 0.189). In males, significant differences were found for phytoene (p = 0.026), phytofluene (p = 0.004), α-carotene (p = 0.034), and β-carotene (p = 0.031). Cmax for total carotenoids (nmol/L ± SD) was positively influenced by WPI (135.4 ± 38.0), while significantly lowered by SPI (89.6 ± 17.3 nmol/L) vs. the control (119.6 ± 30.9, p < 0.001). Tmax did not change. The results suggest that a well-digestible protein could enhance carotenoid bioavailability, whereas the less digestible SPI results in negative effects. This is, to our knowledge, the first study finding effects of proteins on carotenoid absorption in humans.